Dietary Total Antioxidant Capacity and Dietary Polyphenol Intake and Prevalence of Metabolic Syndrome in Polish Adults: A Nationwide Study - Zujko, Małgorzata Elżbieta (Oxid Med Cell Longev, 2018)
Specific classes and subclasses of polyphenols have been studied for their potential effects on noncommunicable diseases, but studies on association between dietary polyphenol intake (DPI) and dietary total antioxidant capacity (DTAC) and MetS (metabolic syndrome) are scarce. Therefore, the aim of this study was to determine associations between DTAC and DPI and the prevalence of MetS and its components in the Polish adult population. Subjects (5690) were participants of the Polish National Multicentre Health Examination Survey (WOBASZ II study) performed in 2013-2014. MetS was defined according to the International Diabetes Federation (IDF) and the American Heart Association/National Heart, Lung, and Blood Institute (AHA/NHLBI) criteria. Daily food consumption was assessed by 24-hour dietary recall. DTAC and DPI were evaluated using the data of food consumption and antioxidant potential of foods, measured by FRAP (ferric reducing antioxidant potential) method, and total polyphenol content in foods, measured by Folin-Ciocalteu assay. Logistic regression models were used to assess the relationship between DTAC and DPI and MetS and its components. Crude, age-adjusted, and multivariable-adjusted models were performed. This study demonstrated that in Polish women, high DPI and high DTAC were significantly associated with a reduced odds ratio for the prevalence of MetS components, such as elevated blood pressure and diabetes. In contrast, in men, high DPI and high DTAC did not have the potential to alleviate MetS components.